Ontogenetic changes in the tyrosine hydroxylase immunoreactive preoptic area in the small-spotted catshark Scyliorhinus canicula (L., 1758) females: catecholaminergic involvement in sexual maturation - Porceddu, Riccardo; Porcu, Cristina; Mulas, Giovanna; Spiga, Saturnino; Follesa, Maria Cristina (Frontiers in Neuroanatomy, 2024)
Introduction The catecholaminergic component of the brain-pituitary-gonadal axis, which mediates the influence of external and internal stimuli on the central nervous system and gonad development in vertebrates, is largely unexplored in Chondrichthyes. We considered Scyliorhinus canicula (L., 1758) females as a model for this vertebrate's class, to assess the involvement of the catecholaminergic system of the brain in its reproduction. Along the S. canicula reproductive cycle, we characterized and evaluated differences in somata morphometry and the number of putative catecholaminergic neurons in two brain nuclei: the periventricular preoptic nucleus, hypothesized to be a positive control for ovarian development, and the suprachiasmatic nucleus, examined as a negative control. Materials and methods 16 S. canicula wild females were sampled and grouped in maturity stages (immature, maturing, mature, and mature egg-laying). The ovary was histologically processed for the qualitative description of maturity stages. Anti-tyrosine hydroxylase immunofluorescence was performed on the diencephalic brain sections. The immunoreactive somata were investigated for morphometry and counted using the optical fractionator method, throughout the confocal microscopy. Results and discussions Qualitative and quantitative research confirmed two separate populations of immunoreactive neurons. The modifications detected in the preoptic nucleus revealed that somata were more numerous, significantly smaller in size, and more excitable during the maturing phase but decreased, becoming slightly bigger and less excitable in the egg-laying stage. This may indicate that the catecholaminergic preoptic nucleus is involved in the control of reproduction, regulating both the onset of puberty and the imminent spawning. In contrast, somata in the suprachiasmatic nucleus grew in size and underwent turnover in morphometry, increasing the total number from the immature-virgin to maturing stage, with similar values in the more advanced maturity stages. These changes were not linked to a reproductive role. These findings provide new valuable information on Chondrichthyes, suggesting the existence of an additional brain system implicated in the integration of internal and environmental cues for reproduction.